(untitled) (Philological Studies, 2019)
In the present paper there is discussed the role of frequency effect in language universals and typology studies. In quantitative typological works the frequency acts as a quantitative measure for an investigation of statistical dependences between language phenomena. In other words, the frequency acts here only as a tool of meta- analysis. The experience of the development of typological direction in linguistics, the experience of the quantitative analysis in psycholinguistics allows to extend the interpretive base of «frequency effect» and to consider it as a part of cognitive processes, as a tool of the mind.